Effect on Stance Phase Timing Asymmetry in Individuals with Amputation Using Hydraulic Ankle Units. Issue 1 (January 2016) - Moore, Raymond
ABSTRACT: Background: Ever since their release, prosthetic feet with integrated hydraulic ankle units have proved a popular prescription choice among individuals with amputation, as quantified in previous studies. One theory is that these types of prosthetic feet lead to a more symmetrical gait pattern. To assess this, we decided to evaluate one of the parameters of gait, the duration of stance phase, and the difference in dominant and nondominant sides. Materials and Methods: A mixture of 22 K2 and K3 individuals with amputation (US Centers for Medicare & Medicaid Services activity level scale) who were due to have their prosthetic feet upgraded to a foot with hydraulic ankle unit as part of their existing treatment had their gait assessed on the pressure plate to establish the difference in stance phase duration between their dominant and nondominant foot. The patients were then reassessed on the pressure plate after a 4-week trial on the feet with hydraulic ankle units. The difference in stance phase durations was again measured and compared with the initial readings. Results: Of the 22 patients assessed, 6 were removed from the case series because of rejection of the device or incompatibility with the pressure measurement equipment. Of the remaining 16 patients, the difference in stance phase timing increased in 2 patients, remained unchanged in 2 patients, and decreased for the other 12 patients. Conclusion: The results showed a statistically significant reduction in asymmetry of stance phase duration when using prostheses that included a foot with a hydraulic ankle unit. This improvement was irrespective of the patients' activity level.